Ischemic colitis presenting as a colonic mass: a case report and diagnostic challenges - Xu, Lin; Wu, Yuqi; Li, Shangjin; Chen, Xinbo; Zhang, Dong; Chen, Boqian; Guo, Shaoju (Frontiers in Medicine, 2025)
Ischemic colitis (IC) is a multifaceted condition that often manifests with nonspecific symptoms such as abdominal pain and bloody diarrhea, particularly in older adults with vascular risk factors. Diagnosis is supported by elevated levels of white blood cells, lactate, and C-reactive protein (CRP). Computed tomography (CT) imaging typically reveals wall thickening and fat stranding in watershed areas. Colonoscopy may demonstrate mucosal erythema, ulceration, or necrosis. IC can be differentiated from inflammatory bowel disease (IBD), diverticulitis, and colorectal cancer based on symptom patterns and imaging findings. The absence of specific biomarkers can complicate diagnosis, potentially causing delays. Illustrating these challenges is the case of a 53-year-old male patient who arrived at the hospital exhibiting abdominal pain and diarrhea. Enhanced CT scans and colonoscopy identified a mass in the ileocecal region of the colon, and subsequent tissue biopsy revealed ischemic lesions in the submucosa. Initially diagnosed with IC, the patient’s symptoms gradually improved with conservative treatment, which included antibiotics, fluid resuscitation, and bowel rest. Follow-up endoscopy showed significant lesion improvement, and no recurrence was detected during subsequent follow-ups. This case illustrates the healing process of IC as manifested by colon mass under endoscopy. Also, it highlights the critical importance of timely diagnosis and personalized treatment strategies in atypical presentations to improve patient outcomes.